Internet of Things Technology Development - Amy Sulastri (Pusat Teknologi Informasi dan Pangkalan Data IAIN Syekh Nurjati Cirebon, 2019)
Internet of Things (IoT) refers to the existence of widely interconnected and widely identified physical devices. The purpose of this tool is to collect data and encourage actions to increase productivity, and ultimately reduce or eliminate dependence on human intervention for data acquisition, interpretation, and use. IoT devices can be sensors or actuators. This survey paper aims to gather and summarize some of the latest library resources on the Internet of Things (IoT) devices. From the results of a paper survey, IoT devices can be grouped into twelve categories, namely: temperature, pressure, flow, level, imaging, noise, air pollution, proximity and displacement, infrared, humidity and humidity, speed, gas and chemicals.